Dualism Meaning of Tat Tvam Asi Concept; Implication Toward Social Stratification System in Hinduism - Syamsul Hadi Untung; Harits Mu'tasyim (Institut Hindu Dharma Negeri Denpasar, 2020)
Humans always connected with other creations and God in his life. Besides, religion becomes the solution for connecting both are; include Hinduism religion. The concept of Tat Tvam Asi is one of the teachings in Hinduism implemented in daily life. This concept also called “Thou Art That” or that is you, which refer to God and human being. It becomes the proper teaching in Hinduism based on theology and philosophy of the worshipers. Besides, there is a social stratification system in Hinduism. This research purposed to reveal the definition, position, source and application of Tat Tvam Asi. Researcher uses the method of descriptive and analysis to explore this concept deeply. At least; this concept has the dual meaning; deity and social. Each meaning has different definition, position, and application except for the source both are referring to one source. The Tat Tvam Asi teaching is no-limit moral teaching which means “He is You” which refer to dual meaning of God or social with different position, application and it’s implication toward social stratification system